Utilization of Grinding Machine Technology to Improve Shrimp Paste Production Capacity in Kecamatan Medan Belawan - Maulana, Bagoes; Solihin, Muhammad Dani; Widarma, Adi; br Barus , Eviyona Laurenta; Dalimunthe, Amirhud (Journal of Community Research and Service, 2025)
Located in Kelurahan Belawan I, Kecamatan Medan Belawan, Kampung Nelayan Lingkungan XII is a coastal area where the community primarily engages in fishing, boat rental services, and producing shrimp paste (terasi) from small shrimp (udang rebon). Observations and discussions with Kelompok Usaha Lestari, a local group dedicated to shrimp paste production, revealed that traditional methods, such as using mortars and pestles, are still prevalent. This manual process significantly limits production capacity and results in inconsistent product quality that deteriorates quickly over time. This Community Partnership Program (PKM) aims to address these issues by improving production efficiency and enhancing product quality through the integration of appropriate technology. The initiative includes the provision of a grinding machine tailored for processing small shrimp, training on product standardization, and continuous guidance to ensure effective use of the technology. The implementation of this technological solution has proven effective in increasing production capacity and ensuring higher consistency and quality of the shrimp paste. These improvements enable Kelompok Usaha Lestari to compete more effectively in the market and contribute to their long-term economic sustainability.